FORMATIVE ASSESSMENT: Indonesian EFL Teachers' Beliefs and Practices - Devi Andriyani, - (2023)
Assessment should be undertaken to examine students' knowledge, attitudes, and skills, as per the recommendations of the 2013 Curriculum. Since the assessment is important to measure the student's knowledge, attitudes, and skills, educators are tasked with creating and administering suitable assessments. Preliminary studies on EFL teachers revealed that teachers' beliefs influence the success or failure of formative assessment practice. However, the phenomenon of teachers' beliefs and practices of formative assessment in the Indonesian EFL classroom context and the techniques used by the teachers is still limited. Therefore, this study aims to examine teachers' beliefs on formative assessment in Indonesian EFL classrooms context, to explore what extent the teachers' beliefs are practiced in the assessment, and to explore the techniques of formative assessment teachers use in the classroom. This study is a case study that is obtained by using interviews and observation checklist analysis. Further, this research was employed by two English teachers as the participants in one of the Junior High Schools in Tembilahan, Indragiri Hilir. Thus, the result of this study is including teachers' several beliefs of formative assessment can help them adjust their teaching style so that they may meet the educational requirements of their students; the use of formative assessment is consistent with the teacher's beliefs about the importance of formative assessment to the instructional process and to the student's progress toward their learning objectives such as provides them with information about where their students are in the learning process and enable them to bring those students closer to the learning objective; and the techniques of formative assessment that teachers use in the classroom deal with the teachers provide clear learning targets, the teacher applied daily test as diagnosing tools to gain students' mastery information, feedback as an essential part of formative assessment and students are involved in the assessment process.